Understanding commanders' information needs for influence operations - Larson, Eric V. (Eric Victor), 1957- (Rand Corporation monograph series, 2009)
Documents a study whose goals were to develop an understanding of commanders' information requirements for cultural and other "soft" factors in order to improve the effectiveness of combined arms operations, and to develop practical ways for commanders to integrate information and influence operations activities into combined arms planning/assessment in order to increase the usefulness to ground commanders of such operations.